The Effect of Special Exercises in some Physical & Coordination Abilities in Futsal - kamil, wameedh; Khalaf, Sabah (Journal of Physical Education, 2025)
Futsal is one of the games that needs high physical abilities & perfect preparation to make the player faced the difficulties in the match. The player of futsal must have high physical & coordination abilities to do the basic skills of the futsal game because this game obligates the player to be ready for attack and defend in the same time add to that this game is being developed in coaching sessions from team to team, Through the watching of the classes of futsal by the researcher because he is one of the teachers in this game, he saw some weakness in some physical and coordination abilities that means there is no focus on them, So the researcher design special exercises to develop them and then develop the performance. The researcher used experimental method to solve the problem and achieve the goals and used pre-test and post-test. The sample of the research are the students of fourth class of physical education and sport science department in Jihan university and they are (14), the percentage is (77%). The researcher does some personal interview with some expert add to the expert of the researcher himself to choose the physical & coordination abilities. The results of the research are the developing of all research variables.